Pengaruh Model Pembelajaran Quick On The Draw Terhadap Peningkatan Aktivitas dan Hasil Belajar Peserta Didik pada Mata Pelajaran IPA Kelas VIII SMPN 13 Padang - Azzahra Sherlyani (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2019)
This research is based on the problems that exist in Padang Public Middle School 13,namely teacher-centered learning, learning activities was lowered and student learning abilities are still low. The effort that can be done is to apply the Quick On The Draw learning model at Padang Middle School 13. The purpose of this study was to determine the effect of applying the Quick On The Draw learning model on the students activities and learning competencies of Grade VIII students of SMP 13 Padang. This study was an experimental study with a randomized control group design posttest only design. The study population was grade VIII students of SMP 13 Padang in the 2019/2020 academic year which spread to eight classes. The research sample was taken using purposive sampling. The results were selected class VIII.6 as the experimental class and class VIII.9 as the control class. In student learning activities the average percentage of the experimental class was 74.95% and the control class was 48.51 The hypothesis in this study was tested using the t-test. The results of the study using the t-test can be concluded that the competency of students knowledge about the value of tcount 5,04 > t table 1.68, the competency of tcount 4,18 > t table 1.68, and competency skills t count 2,17 > t table 1, 68. This shows that the hypothesis is accepted. So, it can be concluded that the application of the Quick On The Draw learning model can improve the students activities and competency of knowledge, attitudes, and skills of grade VIII students of SMP 13 Padang.